2022
DOI: 10.1111/eje.12852
|View full text |Cite
|
Sign up to set email alerts
|

Embedding environmental sustainability within oral health professional curricula—Recommendations for teaching and assessment of learning outcomes

Abstract: The oral healthcare sector is not currently considered to be environmentally sustainable; it is a significant contributor to global greenhouse gas emissions, produces other pollutants, and generates unrecyclable waste. 1 In response to the impact of the wider healthcare sector on the environment, multiple national and international stakeholders have produced policy documents in response to the climate emergency. Such examples include the Paris Agreement, 2 the United Nations Sustainable Development Goals, 3 WH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 24 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…Some topics included in Figure 2 are well established in OHP education and others are more emergent areas of interest. There are published recommendations to support OHP schools in embedding some of these concepts in the curriculum, although they are limited to certain topics 30,32 . These documents largely include learning outcomes and recommendations for learning, teaching and assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some topics included in Figure 2 are well established in OHP education and others are more emergent areas of interest. There are published recommendations to support OHP schools in embedding some of these concepts in the curriculum, although they are limited to certain topics 30,32 . These documents largely include learning outcomes and recommendations for learning, teaching and assessment.…”
Section: Discussionmentioning
confidence: 99%
“…There are published recommendations to support OHP schools in embedding some of these concepts in the curriculum, although they are limited to certain topics. 30,32 These documents largely include learning outcomes and recommendations for learning, teaching and assessment. It is noted that there is an absence of guidance for some top-…”
Section: Integration Of Topics Of Interestmentioning
confidence: 99%
“…During the annual meeting of the Association for Dental Education in Europe (ADEE) in 2019, a special interest group (SIG) published a consensus view shedding light on how essential is ESD in dental education and that awareness should be raised concerning the need for educator’s support in developing ESD curricula [ 15 ]. Following the recent annual ADEE meeting of the SIG, in 2021, a consensus article was published [ 23 ], reporting the European consensus on suggested learning outcomes for ESD concerning the Graduating European Dentist curricula, providing recommendations for teaching ESD within existing OHP programmes, including methods of teaching and assessment. The outcomes of the ADEE SIG consensus meeting [ 23 ] suggested that the incorporation of ESD into OHP education poses challenges due to an already overloaded curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…Following the recent annual ADEE meeting of the SIG, in 2021, a consensus article was published [ 23 ], reporting the European consensus on suggested learning outcomes for ESD concerning the Graduating European Dentist curricula, providing recommendations for teaching ESD within existing OHP programmes, including methods of teaching and assessment. The outcomes of the ADEE SIG consensus meeting [ 23 ] suggested that the incorporation of ESD into OHP education poses challenges due to an already overloaded curriculum. To address this, a student-centred approach with practical resources and materials is necessary to help students and educators develop a basic understanding of ESD.…”
Section: Discussionmentioning
confidence: 99%
“…During the annual meeting of the Association for Dental Education in Europe (ADEE) in 2019, a Special Interest Group (SIG) published a consensus view shedding light on how essential is ESD in dental education and that awareness should be raised concerning the need for educator's support in developing ESD curricula [14]. Following the recent annual ADEE meeting of the SIG, in 2021, a consensus article was published [19], reporting the European consensus on suggested learning outcomes for ESD concerning the Graduating European Dentist (GED) curricula, providing recommendations for teaching ESD within existing Oral Health Professional (OHP) programmes including methods of teaching and assessment.…”
mentioning
confidence: 99%